2022
DOI: 10.1111/ejn.15870
|View full text |Cite|
|
Sign up to set email alerts
|

Reactivity to conditioned threat cues is distinct from exploratory drive in the elevated plus maze

Abstract: The funder did not have any additional role in study design, data collection and analysis, decision to publish, or preparation of the article. There are no patents, products in development, or marketed products to declare.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We did not find any relation of vigilance screen behaviour to behaviour in the elevated plus maze, a task widely used to model the avoidance symptoms of anxiety disorders. We recently demonstrated a relative independence of measures from aversive conditioning and the EPM exploration (18), which supports that these tasks reveal different behavioural strategies for dealing with potential threats. Rats have been successfully studied as models for affective state biases in choice behaviours (2123).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…We did not find any relation of vigilance screen behaviour to behaviour in the elevated plus maze, a task widely used to model the avoidance symptoms of anxiety disorders. We recently demonstrated a relative independence of measures from aversive conditioning and the EPM exploration (18), which supports that these tasks reveal different behavioural strategies for dealing with potential threats. Rats have been successfully studied as models for affective state biases in choice behaviours (2123).…”
Section: Discussionmentioning
confidence: 59%
“…The following day, a vigilance screen was performed where one group were presented with the tone CS twice at a low volume (Low Vol) to reduce its salience. The levels of time spent in the closed arm during the EPM test did not significantly correlate with behaviour at the later Vigilance Screen (P=0.9870), suggesting the two tests measure distinct reactions to threats (18). At the first presentation of the Low Vol CS, freezing responses were significantly lower as a group than those presented a Norm Vol CS as expected (P=0.0083, Fig1c).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Research has shown that the recall of aversive memories, such as those associated with conditioned threat cues, can potentiate anxiety-like behavior in rodents. This suggests that subtle cues, reminiscent of microaggressions, can have significant impacts on behavior [111]. By incorporating these cues into rodent models, researchers can better mimic the nuanced social stressors experienced by humans.…”
Section: Study Microaggressions Through Subtle Threat Cuesmentioning
confidence: 99%
“…Distinct motivations to freeze are evident across assays; freezing on one task will not necessarily predict freezing on another. For example, freezing during context conditioning does not predict freezing on an elevated plus maze (Ahn et al, 2013 ; Hilton et al, 2023 ). Thus, the same mechanisms that lead to freezing during fear conditioning do not necessarily contribute to freezing on more exploratory-based behavioral assays, supporting the observation that multiple neural circuits can trigger this behavioral state (Zelikowsky et al, 2018 ).…”
Section: Box 1: Considerations For Interpreting Measures Of Fear and ...mentioning
confidence: 99%